SuperSelf doubling your personal effectiveness - Givens, Charles J (Simon & Schuster, 1993)
Charles J. Givens is world-famous for his unique, practical, and powerful strategies that have helped millions of people along the road to success and financial freedom. He has made publishing history as the author of three number-one best-selling financial self-help books, Wealth Without Risk, Financial Self-Defense, and More Wealth Without Risk, with record-breaking total sales of over three million hardcover.